SOSIALISASI APLIKASI GOOGLE FAMILY LINK SEBAGAI PENGAWASAN TERHADAP ANAK DALAM MENGGUNAKAN GAWAI PADA TK ISLAM WAHYU BHAKTI - Puspitasari, Anggun Citra Dini Dwi; Rahmawati; Karyati, Zetty (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2023)
The purpose of this community service activity is to provide outreach to the parents and teachers of the Wahyu Bhakti Islamic Kindergarten, East Jakarta about the Google Family Link application as a means of supervising children in using the gadget. The implementation methods we use are observation, interviews, outreach, training, and evaluation. We provide this socialization and training by providing direct understanding and training about using the Google Family Link application. After socialization and training, the parents and teachers of Wahyu Bhakti Islamic Kindergarten have begun to understand and be able to access and apply Google Family Link.